Acute ingestion of a high-fructose drink impairs vascular autonomic modulation and reflex control of blood pressure in first-degree relatives of diabetic patients. (July 2021) - Dipp, T.; Moraes-Silva, I.C.; Dos Santos, F.; Casali, K.R.; Morris, M.; Signori, L.U.; De Angelis, K.; Aletti, F.; Irigoyen, M.C.; Plentz, R.D.M.; Schaan, B.D.
Abstract: First-degree relatives of diabetes patients, despite being euglycemic, presented impaired BRS and exacerbation of sympathetic modulation after ingestion of a high fructose drink when challenged to orthostatic stress. This finding alerts the importance of early autonomic dysfunction even in clinically healthy people, especially in face of a stressful situation.